Learning needs of Comprehensive General Medicine Specialists for the care of suicidal behavior - Dinorah Janet Torres Lugo; Mabel Rocha Vázquez; Idalberto Amado Pérez López; Iván Castillo Ledo; Antonio Masot Rangel; Silvia Janet Masó Torres (Medisur)
Foundation: suicidal behavior is an important public health problem, Cuba has included the topic in the study plans to improve its care. However, it is noted that there are learning needs for its care by specialists in Comprehensive General Medicine. Objective: to identify the Comprehensive General Medicine specialists’ learning needs for the care of suicidal behavior. Methods: a descriptive, cross-sectional observational study was carried out in the Cienfuegos province from January to December 2022. A sample of 379 professionals was selected through simple random sampling. For the diagnosis, empirical methods were applied, validated by expert criteria and a pilot test. Results: the instruments showed that 100% of the Comprehensive General Medicine specialists are unaware of the National Program for the Prevention and Control of Suicidal Behavior actions; they presented problems in the quality of the follow-up of suicidal behavior and its identification as a priority health problem. Between 98 and 100% considered their knowledge of suicidal behavior to be insufficient and evaluated their performance as improvable or not adequate. Conclusions: the Comprehensive General Medicine specialists present learning needs for the care of suicidal behavior in terms of: health promotion and prevention, actions of the National Program for the Prevention and Control of Suicidal Behavior, its identification as a priority health problem to plan promotion, prevention and rehabilitation actions at the individual, family and community level.